Estimated impact of hepatitis C–positive lung donor utilization on US donor lung supply. Issue 1 (5th September 2019) - Mooney, Joshua J.; Purington, Natasha; Mohabir, Paul; Dhillon, Gundeep S.
Abstract : The availability of highly effective direct‐acting antiviral agents (DAAs) for hepatitis C virus (HCV) infection has led to reports of safely transplanting HCV + donor lungs into HCV − candidates. However, it remains unclear how the ability to use HCV + donor lungs for lung transplant could affect the number of donor lungs available for transplant. Using Scientific Registry of Transplant Recipient data, we identified all deceased organ donors within the United States from March 1, 2015, to February 28, 2018, and stratified by HCV status. A donor prediction model for lung donation was derived and validated within HCV − donors and applied to HCV + donors to estimate the number of acceptable HCV + lung donors. Of 29 481 eligible donors, 2054 (7.0%) were HCV + donors with 82 HCV + donors' lungs being used for transplant during the study period. The prediction model for donor lung donation (specificity 92.6%, sensitivity 65.6%) estimated 248 HCV + donors (75 nonviremic, 173 viremic) were acceptable for lung transplant during the study period, suggesting that 166 acceptable HCV + lung donors were discarded. The ability to transplant lungs from HCV + organ donors would lead to an estimated nationwide increase of at least 55 donor lungs per year, including 44 from HCV viremic donors. Abstract : The authors demonstrate that improved utilization of hepatitis C virus–positive donor lungs would increase the donor lung supply within the United States.